RANCANG BANGUN APLIKASI RENTAL DAN E-TICKETING TAKSI DI WILAYAH KALIMANTAN BARAT BERBASIS WEB - Mukti, Surya (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Abstract-Rental Application and E-Ticketing Taxi web-based West Kalimantan, is a system application taxi ticket sales and rentals. The system is made to the customer in finding a taxi ticket or hire a taxi to travel to the destination and also made for a taxi company in marketing the ticket. The system is constructed by applying the technique of responsive web design so that the display can adjust the size of the cotton area of the browser used by the user. The approach used in the study is a structured approach that uses several tools and construction techniques, such as flowcharts, data flow diagrams, database design and interface design system. Testing the system using black box method. The results of the Rental Application and E-Ticketing Taxi West Kalimantan can help customers in search of tickets and help taxi companies in the ticket as well as a media marketing campaign of the company.Â